Dampak Terpaan Informasi Media Digital terhadap Perkembangan Pariwisata dan Perilaku Masyarakat Bali - I N. Laba; I M.T. Semara; K.R. Tunjungsari (Pusat Kajian Bali Universitas Udayana, 2018)
In this millennial era many tourism industries use digital media as a means of promotion. The digital media has greatly influenced tourism development and community life. Media exposure has a positive and negative impact on its users. Media information exposure can affect the socio-cultural community. It is necessary to master and control information technology to give us benefits. The aim of this study is to determine the impact of media information exposure to the development of tourism and the behavior of Balinese people. The type of data used in this study is quantitative and qualitative deriving from secondary data sources. Data collection techniques use documentation study sourced from government reports and online news media. The results show that exposure of digital media information has a positive and negative impact on the development of tourism and the behavior of Balinese people.